2022
DOI: 10.1177/15910199221106049
|View full text |Cite
|
Sign up to set email alerts
|

Basilar artery occlusion: A review of clinicoradiologic features, treatment selection, and endovascular techniques

Abstract: Basilar artery occlusion (BAO) is an infrequent but often fatal subtype of stroke. Predicting outcomes and selecting patients for endovascular therapy (EVT) remains challenging. Advances in neuroimaging and the development of prognostic scoring systems have augmented clinical decision-making over time. Recent randomized trials, BEST (Basilar Artery Occlusion Endovascular Intervention vs. Standard Medical Treatment), BASICS (Basilar Artery International Cooperation Study), BAOCHE (Basilar Artery Occlusion CHine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 76 publications
(131 reference statements)
0
9
0
1
Order By: Relevance
“…Median CLEOS score (IQR) for the entire cohort was 508 (426-584) and median THRIVE score (IQR) was 4 (3)(4)(5)(6). Characteristics in the good (mRS 0-2) and poor (mRS 3-6) outcome groups are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Median CLEOS score (IQR) for the entire cohort was 508 (426-584) and median THRIVE score (IQR) was 4 (3)(4)(5)(6). Characteristics in the good (mRS 0-2) and poor (mRS 3-6) outcome groups are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the natural history of patients presenting with an acute BAO who do not receive reperfusion therapy is poor, 2 though randomized EVT trials have not universally demonstrated a benefit for thrombectomy. 3 Despite this, EVT remains the standard of care for BAO patients presenting with a disabling neurological deficit in the absence of a large core infarction on initial imaging studies, 3 considering the excellent reperfusion rates with EVT and good outcomes in over 40% of patients reported in meta-analyses. 4,5 Similar to CLEOS, the Totaled Health Risks in Vascular Events (THRIVE) score predicts outcomes for patients presenting with anterior circulation large vessel occlusion (LVO) strokes and was originally derived from the Mechanical Embolus Removal in Cerebral Ischemia (MERCI) and Multi-MERCI clinical trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor outcomes among patients treated with endovascular therapy has been reported in patients with BATMAN <7 [18] . Generalization of these scores is challenging given the retrospective nature of the studies, variable outcome definitions, and small sample sizes [31] . In theory, MRI studies could be used to identify the absolute validity of scores before spending time and effort optimizing issues with beam-hardening and other artifacts which limit posterior fossa gray-white resolution on CT.…”
Section: Imagingmentioning
confidence: 99%
“…急性基底动脉闭塞是急性缺血性脑卒中的严重亚型之一,占颅内大血管闭塞的5%~10%,患者病死率和严重残疾率高达70% [ 1 - 3 ] 。最近两项有关急性基底动脉闭塞血管内治疗的随机对照试验——BAOCHE(Basilar Artery Occlusion Chinese Endovascular)试验 [ 4 ] 和ATTENTION(Endovascular Treatment for Acute Basilar-Artery Occlusion)试验 [ 5 ] 结果显示,中重度急性基底动脉闭塞所致缺血性脑卒中患者机械取栓相比标准药物治疗可以更多获益。《急性缺血性卒中血管内治疗中国指南2023》建议,对发病24 h内的急性后循环大血管闭塞患者,经过临床及影像筛选后,推荐血管内取栓治疗(Ⅰ类推荐,A级证据) [ 6 ] 。可以预见,血管内机械取栓将成为急性基底动脉闭塞患者急性期治疗的一个重要方法。然而,尽管80%~90%在起病24 h内接受血管内治疗的急性基底动脉闭塞患者可以获得血管成功再通(mTICI分级2b~3级),其中仍有超过一半的患者在90 h内临床神经功能结局不良,即发生血管无效再通 [ 7 - 8 ] 。因此,深入研究急性基底动脉闭塞患者血管内治疗后无效再通的发生机制和预测因素,有助于在临床中识别风险因素和保护因素,找到个性化的治疗靶点,减少无效再通发生率,从而改善患者的临床结局。…”
unclassified